2012
DOI: 10.1172/jci58227
|View full text |Cite
|
Sign up to set email alerts
|

Decreased cardiac L-type Ca2+ channel activity induces hypertrophy and heart failure in mice

Abstract: Antagonists of L-type Ca 2+ channels (LTCCs) have been used to treat human cardiovascular diseases for decades. However, these inhibitors can have untoward effects in patients with heart failure, and their overall therapeutic profile remains nebulous given differential effects in the vasculature when compared with those in cardiomyocytes. To investigate this issue, we examined mice heterozygous for the gene encoding the pore-forming subunit of LTCC (calcium channel, voltage-dependent, L type, α1C subunit [Cacn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
113
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(125 citation statements)
references
References 64 publications
(76 reference statements)
11
113
1
Order By: Relevance
“…Consistent with our data, the Ca 2 + channel a1c subunit expression decreased dramatically in the ventricle in ischemic hypertrophic myocardium at 6 weeks after MI (Huang et al, 2008;Goonasekera et al, 2012). In the failing mouse heart, the investigators consistently observed a significant reduction in a1c protein after 8 weeks of pressure overload stimulation (Goonasekera et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with our data, the Ca 2 + channel a1c subunit expression decreased dramatically in the ventricle in ischemic hypertrophic myocardium at 6 weeks after MI (Huang et al, 2008;Goonasekera et al, 2012). In the failing mouse heart, the investigators consistently observed a significant reduction in a1c protein after 8 weeks of pressure overload stimulation (Goonasekera et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, Ca V 1.2 blockers effectively inhibit cardiac remodeling and prevent cardiomyopathy in animal models with pressure overload (41,42). Paradoxically, in light of these experimental results, decreased expression of Ca V 1.2 protein in the heart also leads to heart failure (43). In addition to direct effects on Ca 2+ signaling, changes in Ca V 1.2 protein levels also would alter subcellular dyadic structures in cardiomyocytes that depend on the presence of the Ca V 1.2 protein (44-46) and would modify the level and composition of the supramolecular complex of Ca V 1.2 with other signaling proteins such as the β2-adrenergic receptor, AKAPs, adenylyl cyclases, PKA and other kinases, phosphodiesterases, and phosphoprotein phosphatases, including calcineurin (47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…This reduced exercise capacity of SA mice, plus the changes in intracellular Ca 2+ signaling that result from reduced basal and stimulated Ca V 1.2 current, likely trigger cardiac hypertrophy in SA mice. Previous studies have shown that many changes in Ca-dependent signaling pathways can induce hypertrophy in experimental animals, including changes in Ca 2+ /calmodulin-dependent protein kinase II activity, calcineurin, level of expression of Ca V 1.2 channels, and regulation of Ca V 1.2 channels (4,5,37,38). Remarkably, simply deleting the dCT of Ca V 1.2 channels is sufficient to cause prenatal cardiac hypertrophy and heart failure (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, simply deleting the dCT of Ca V 1.2 channels is sufficient to cause prenatal cardiac hypertrophy and heart failure (16,17). Moreover, both increased and decreased expression of Ca V 1.2 channels can cause hypertrophy and heart failure (37,38), suggesting a precise balance point for healthy cardiac function. Our results reveal that mutation of a single amino acid residue that impairs basal and β-adrenergic regulation of Ca V 1.2 channels is sufficient to induce cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 99%